Ampliação Dialógica nas Demandas Estruturais: Potencialidades e Desafios da Participação dos Tribunais de Contas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This work discusses the possibility of participation of the Audit Courts in structural demands, and the role they can play, considering their competencies, functions and the characteristics of this type of demand. Therefore, the objective is to identify the potential and challenges for such participation, taking into account the peculiarities of structural demands, the limits of action of the Courts of Auditors and the needs encountered by procedural actors. The research addresses issues such as expanding participation and fostering dialogic openness permeate the research developed, as well as consensuality in Public Administration, both in the judicial and administrative spheres and the relationship between structural demands, external oversight activity and public policies. To achieve this objective, the study employs hypothetical- deductive, comparative and observational methods, along with indirect documentary techniques, including literature review and document analysis, and direct documentary techniques, such as case studies, observation, and interviews. It is emphasized that the research considered the translational perspective seeking a constant dialogue between theory and practice, creating a true feedback loop. From the research conducted it was observed that such participation is indeed possible, with one legal action being identified where it occurred. Furthermore, based on the analysis of the documents collected, the case studies and the interviews conducted, it was possible to determine the potential that this type of participation brings, as well as possible challenges and limits to this action. The manuscript concludes by suggesting modes and occasions for participation, based on the data collected, the needs indicated by the procedural actors, and the specificities identified in relation to this type of litigation.
Keywords: Demandas estruturais; Tribunais de Contas; Processo estrutural; Políticas Públicas; Participação; Structural demand; Court of Accounts; Structural process; Public Policies; Participation; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO